Coverage and Determinants of the Success of Antenatal Care (ANC) in First Trimester Pregnant Women at Lubuk Pakam Public Health Center - Nathasia Elga Haryono; Via Wiyana; Martine Agustina Meha; Kurniawati (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
Antenatal Care (ANC) services play a crucial role in the early detection of pregnancy complications, prevention of maternal morbidity and mortality, and overall improvement of maternal and fetal health. High-quality ANC provides opportunities for healthcare providers to conduct screening, health education, and promotive as well as preventive interventions throughout pregnancy. However, its implementation in the field still faces challenges related to service completeness, continuity, and quality. This study aimed to assess the coverage and quality of Integrated Antenatal Care (ANC) services among first-trimester pregnant women at Lubuk Pakam Health Center. A quantitative descriptive design was used with a total sampling technique involving 120 respondents. Data were collected through structured interviews, direct observation, and document review of medical records. The results showed that 78.3% of mothers had attended ANC visits, but only 58.3% received the complete 10T standard services. Laboratory examinations (60%) and referrals (25%) remained below national standards. The dominant factors influencing ANC success were maternal knowledge, family support, and access to health facilities. Therefore, strategies to improve ANC quality should include strengthening laboratory and human resources, providing continuous staff training, and enhancing maternal and family education to ensure optimal and comprehensive antenatal care services.